Hydrogen dilution on an undoped silicon oxide layer and Its application to amorphous silicon thin-film solar cells. (January 2016) - Chen, Yu-Hung; Lin, Chen-Cheng; Liu, Yung-Tsung; Lu, Hsin-Wei; Liu, Jun-Chin
Abstract: This paper proposes the use of undoped hydrogenated microcrystalline silicon oxide (μc-SiO x :H) deposited on an n-μc-Si:H layer of amorphous silicon single-junction superstrate-configuration thin-film solar cells produced using 40 MHz very high frequency plasma-enhanced chemical vapor deposition. We found that undoped μc-SiO x :H thin film under optimized hydrogen dilution conditions had high crystallinity, high conductivity, a wide optical band gap, and a high refractive index, which are advantageous properties in solar cells. However, deposition at higher hydrogen dilutions degraded the quality and optoelectronic properties of the films, because the morphology of the films changed from microcrystalline to amorphous. These results suggest that the use of an optimized undoped μc-SiO x :H layer improves a-Si:H thin-film solar cell performance through enhancement of the short-circuit current density J sc . The increased J sc can be attributed to an improved light-trapping capability in the long wavelength range, between 620 and 680 nm, as demonstrated by the external quantum efficiency. This technique also allows optimal conversion efficiency to be achieved. The results demonstrated that hydrogen dilution plays a dominant role in the improvement of film quality and solar cell performance; however, the tradeoff between refractive index and conductivity must be considered.